Do subjects with aggressive and chronic periodontitis exhibit a different cytokine/chemokine profile in the gingival crevicular fluid? A systematic review. (25th March 2014) - Duarte, P. M.; Bastos, M. F.; Fermiano, D.; Rabelo, C. C.; Perez‐Chaparro, P. J.; Figueiredo, L. C.; Faveri, M.; Feres, M.
<x xml:space="preserve">Abstract</x> Background and Objective Microbiological and immunological hypotheses have been raised to explain the differences in the clinical manifestations of aggressive periodontitis and chronic periodontitis. However, studies comparing the cytokine/chemokine profiles in gingival crevicular fluid between these two clinical conditions have so far not been compiled. This systematic review aimed to answer the following question: "Do subjects with aggressive periodontitis and chronic periodontitis have a different profile of cytokines/chemokines in the gingival crevicular fluid?" Material and Methods An electronic database search of MEDLINE/PubMed and Embase was performed from 1990 up to and including August 2013, using MeSH terms and other keywords. Titles and abstracts were screened and the papers that satisfied eligibility criteria were assessed. Results Of 1954 titles, 17 studies reporting the levels of 21 different cytokines/chemokines were included. Most studies did not find any significant differences in the gingival crevicular fluid levels of cytokines/chemokines between aggressive periodontitis and chronic periodontitis. Some studies demonstrated that the levels of specific proinflammatory and anti‐inflammatory cytokines/chemokines were higher (n = 5) and lower (n = 3), respectively, in aggressive periodontitis than in chronic periodontitis. The studies differed in the manner in which they reported the results (e.g. concentrations or total amounts). It was not clear in some studies whether the sample sites from both groups were matched for disease severity. Some studies did not take into account confounders, such as smoking. Conclusion The current weight of evidence is not sufficient to prove that there are distinct gingival crevicular fluid cytokine/chemokine profiles for patients with aggressive periodontitis and chronic periodontitis.